The Influence of Temperature on the Antiviral Response of mIgM+ B Lymphocytes Against Hirame Novirhabdovirus in Flounder (Paralichthys olivaceus) - Tang, Xiaoqian; Ma, Xinbiao; Cao, Jing; Sheng, Xiuzhen; Xing, Jing; Chi, Heng; Zhan, Wenbin (Frontiers in Immunology, 2022)
Hirame novirhabdovirus (HIRRV) is an ongoing threat to the aquaculture industry. The water temperature for the onset of HIRRV is below 15 ℃, the peak is about 10 ℃, but no mortality is observed over 20 ℃. Previous studies found the positive signal of matrix protein of HIRRV (HIRRV-M) was detected in the peripheral blood leukocytes of viral-infected flounder. Flow cytometry and indirect immunofluorescence assay showed that HIRRV-M was detected in mIgM+ B lymphocytes in viral-infected flounder maintained at 10 ℃ and 20 ℃, and 22% mIgM+ B lymphocytes are infected at 10 ℃ while 13% are infected at 20 ℃, indicating that HIRRV could invade into mIgM+ B lymphocytes. Absolute quantitative RT-PCR showed that the viral copies in mIgM+ B lymphocytes were significantly increased at 24 h post infection (hpi) both at 10 ℃ and 20 ℃, but the viral copies in 10 ℃ infection group were significantly higher than that in 20 ℃ infection group at 72 hpi and 96 hpi. Furthermore, the B lymphocytes were sorted from HIRRV-infected flounder maintained at 10 ℃ and 20 ℃ for RNA-seq. The results showed that the differentially expression genes in mIgM+ B lymphocyte of healthy flounder at 10 ℃ and 20 ℃ were mainly enriched in metabolic pathways. Lipid metabolism and Amino acid metabolism were enhanced at 10 ℃, while Glucose metabolism was enhanced at 20 ℃. In contrast, HIRRV infection at 10 ℃ induced the up-regulation of the Complement and coagulation cascades, FcγR-mediated phagocytosis, Platelets activation, Leukocyte transendothelial migration and Natural killer cell mediated cytotoxicity pathways at 72 hpi. HIRRV infection at 20 ℃ induced the up-regulation of the Antigen processing and presentation pathway at 72 hpi. Subsequently, the temporal expression patterns of 16 genes involved in Antigen processing and presentation pathway were investigated by qRT-PCR, and results showed that the pathway was significantly activated by HIRRV infection at 20 ℃ but inhibited at 10 ℃. In conclusion, HIRRV could invade into mIgM+ B lymphocytes and elicit differential immune response under 10 ℃ and 20 ℃, which provide a deep insight into the antiviral response in mIgM+ B lymphocytes.